Citation Frequency and the Value of Patented Inventions - Harhoff, Dietmar; Narin, Francis; Scherer, F. M.; Vopel, Katrin (The Review of Economics and Statistics, 1999)
Through a survey, private economic value estimates were obtained on 964 inventions made in the United States and Germany and on which German patent renewal fees were paid to full-term expiration in, 1995. A search of subsequent U.S. and German patents yielded counts of citations to those patents. Patents renewed to full-term were significantly more highly cited than patents allowed to expire before their full term. The higher an invention's economic value estimate was, the more the patent was subsequently cited.